2021
DOI: 10.1007/s12144-021-01827-z
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment and psychopathic traits: Investigating the role of gender, maternal and paternal factors

Abstract: Individuals with psychopathic traits have been identified to display insecure attachment. However, it is not clear which attachment dimension contributes more to high psychopathic traits, and more specifically to callous-unemotional (CU) traits, which parental relationship is more influential and if this differs across gender. This study examined the associations of adult attachment dimensions (avoidance and anxiety) and parental factors (regard, responsibility and control) with CU traits (N = 1149) using Hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(112 reference statements)
0
4
0
1
Order By: Relevance
“…However some studies have found no relationship between psychopathy and attachment (Brennan & Shaver, 1998). Furthermore findings seem to differ regarding the specific association with primary and secondary psychopathic traits and avoidant and anxiety attachment in clinical and non-clinical populations due to the different conceptualizations of psychopathy and insecure attachment dimensions (Brewer et al, 2018;Conradi et al, 2016;Kyranides et al, 2021;Mack et al, 2011;Schimmenti et al, 2014).…”
Section: Primary and Secondary Psychopathic Traitsmentioning
confidence: 97%
See 1 more Smart Citation
“…However some studies have found no relationship between psychopathy and attachment (Brennan & Shaver, 1998). Furthermore findings seem to differ regarding the specific association with primary and secondary psychopathic traits and avoidant and anxiety attachment in clinical and non-clinical populations due to the different conceptualizations of psychopathy and insecure attachment dimensions (Brewer et al, 2018;Conradi et al, 2016;Kyranides et al, 2021;Mack et al, 2011;Schimmenti et al, 2014).…”
Section: Primary and Secondary Psychopathic Traitsmentioning
confidence: 97%
“…The attachment framework has been adopted by a variety of researchers in an effort to understand the developmental and environmental risk factors as well as the etiological origins of psychopathic traits (Conradi et al, 2016;Hong et al, 2016;Kyranides et al, 2021;Saltaris, 2002;Schimmenti et al, 2014). Studies have proposed that early maladaptive and insecure child-parent attachment (resulting from maternal deprivation, adverse childhood experiences) give rise to dysfunctional internal working models characterized by mistrust, lack of empathy and affect, which in turn increase the likelihood of the emergence of psychopathic traits (Blanchard & Lyons 2016;Kyranides et al, 2021;Saltaris, 2002;Schimmenti et al, 2014). However some studies have found no relationship between psychopathy and attachment (Brennan & Shaver, 1998).…”
Section: Primary and Secondary Psychopathic Traitsmentioning
confidence: 99%
“…Preciznije, pokazalo se da osobe sa izbegavajućim i bojažljivim stilom ostvaruju više skorove na merama primarne i sekundarne psihopatije u poređenju sa ispitanicima koje karakteriše siguran stil afektivne vezanosti (Alzeer et al, 2019). Druge studije takođe ukazuju na to da izbegavajući obrazac afektivnog vezivanja predstavlja faktor rizika za manifestaciju osobina koje se povezuju sa psihopatijom, posebno sa njenom afektivnom dimenzijom (Kyranides et al, 2021;Walsh et al, 2019). Važno je, međutim, naglasiti da utvrđena korelacija između nesigurne afektivne vezanosti i psihopatskih tendencija svakako ne rasvetljava pitanje kauzalnosti.…”
Section: Odnos Između Tipova Afektivne Vezanosti I Psihopatoloških Si...unclassified
“…Alternatively, avoidantly attached adult individuals are defined by their attempts to render the system of attachment through methods such as emphasizing self-sufficiency, avoiding emotional closeness, denying their attachment needs, and maximizing their physical and emotional distance from others 26,27 . Predictably, insecure adult attachment dimensions have been related to symptoms of depression and anxiety or psychopathic traits [28][29][30][31] .…”
mentioning
confidence: 99%